Hybrid molecule between platanic acid and LCL-161 as a yes-associated protein degrader. (25th February 2022) - Nakano, Naoko; Fukuda, Kazuo; Tashiro, Etsu; Ishikawa, Haruka; Nagano, Waka; Kawamoto, Rie; Mori, Alice; Watanabe, Misao; Yamazaki, Ryu; Nakane, Takahisa; Naito, Mikihiko; Okamoto, Iwao; et al.
Abstract: Dysregulated yes-associated protein (YAP) is involved in several malignant cancers. However, discovering a druggable YAP inhibitor(s) is difficult because YAP itself does not have any enzymatic activity. In such cases, targeted protein degradation strategies based on hybrid molecules that bind to the target protein and an E3 ubiquitin ligase are useful for suppressing proteins that exhibit aberrant activation and/or excessive expression. Upon screening YAP-interacting small compounds, we identified HK13, a platanic acid, as a novel compound that interacts with YAP. Next, we synthesized hybrid compounds of platanic acid and LCL-161, which reportedly shows a high affinity for cIAP, one of E3 ubiquitin ligases. Among these compounds, HK24 possessed the ability to inhibit the growth of YAP overexpressing NCI-H290 cells. This inhibitory activity may be mediated by YAP degradation, although HK24 exhibited weak YAP degradation. Furthermore, we confirmed involvement of proteasome pathway in HK24-dependent YAP degradation by culturing NCI-H290 cells in the presence of a proteasome inhibitor. Therefore, it is possible that platanic acid is a potential candidate for molecular medicine targeting YAP. Graphical Abstract: